Antibiotic resistance in enteric Escherichia coli and Enterococcus spp. isolated from ungulates at Marwell Zoo England - Jansen van Vuuren, M. (University of Pretoria, 2017)
Dissertation (MSc)--University of Pretoria, 2016.